(untitled) (Research, Society and Development, 2021)
The objective of the research was to characterize the commercialization of cucurbits in open markets in São Luís-MA, to provide information about the attributes of these vegetables and the limitations in their commercialization, and also to outline a socioeconomic profile of the marketers. The research was carried out in five open markets located in five neighborhoods of the city (Cidade Operária, Cohab, João Paulo, Angelim and Mangueirão), the data collection was carried out through semi-structured questionnaires. The data were tabulated using Microsoft Excel to analyze and interpret the results. From the results it was found that men have more participation (58%) in the sale of cucurbits and women (42%); in relation to income, 8% receive less than one minimum wage per month, 52% receive up to three wages and 10% more than three wages. With regard to production, it was found that 65% do not produce the cucurbits they sell, 40% being supplied by other states, despite Maranhão being self-sufficient in the production of most cucurbits consumed by its population. The most striking presence at the fairs were Cucumis anguria L. and Cucumis sativus var. sativus L. Most of them are exposed at fairs around 1 to 24 hours, after that period, when not sold, they can generate losses. Among the main problems in commercialization, the most cited was the competition that may be linked to the price and the low variety of products. He observed that 48% of marketers have low technical knowledge. It is necessary to invest in basic marketing courses for marketers in order to guide them in choosing the best marketing strategies and to break this limitation.